2010
DOI: 10.1186/1742-2094-7-11
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral changes of TNF-α and IL-10 protein in the lumbar and cervical dorsal root ganglia following a unilateral chronic constriction injury of the sciatic nerve

Abstract: BackgroundThere is a growing body of evidence that unilateral nerve injury induces bilateral response, the mechanism of which is not exactly known. Because cytokines act as crucial signaling molecules for response of peripheral nerves to injury, they may be induced to mediate the reaction in remote structures.MethodsWe studied levels of tumor necrosis factor α (TNF-α) and interleukin 10 (IL-10) proteins using ELISA in the ipsilateral and contralateral lumbar (L4-L5) and cervical (C7-C8) dorsal root ganglia (DR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
64
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(72 citation statements)
references
References 75 publications
8
64
0
Order By: Relevance
“…Sun T et al 43 also observed that the changes of mechanical and thermal pain thresholds and spinal TNF-α and IL-1β mRNA expression were isochronous, and effective suppression on CCI-induced up-regulation of TNF-β mRNA and IL-1α mRNA expression might be conducive to reduce mechanical allodynia and thermal hyperalgesia in neuropathic pain rats. These findings were coincident with the study of Jancálek R and so on 44-46. Thus, we believed that TNF-α and IL-1β might mediate the CCI-induced allodynia.…”
Section: Discussionsupporting
confidence: 89%
“…Sun T et al 43 also observed that the changes of mechanical and thermal pain thresholds and spinal TNF-α and IL-1β mRNA expression were isochronous, and effective suppression on CCI-induced up-regulation of TNF-β mRNA and IL-1α mRNA expression might be conducive to reduce mechanical allodynia and thermal hyperalgesia in neuropathic pain rats. These findings were coincident with the study of Jancálek R and so on 44-46. Thus, we believed that TNF-α and IL-1β might mediate the CCI-induced allodynia.…”
Section: Discussionsupporting
confidence: 89%
“…5). This fact is supported by an earlier observation that IL-10 can suppress synthesis of proinflammatory cytokines, such as TNF-alpha, IL-6, and IL-1 by targeting circulating immune cells, liver, and spleen [56], [57], and can down-regulate receptors for proinflammatory cytokines [58]. We detected a slight increase in serum IL-10 as early as 1 h after LPS injection.…”
Section: Discussionsupporting
confidence: 83%
“…2). Upregulation of TNFα transcription in DRG neurons is in the line with studies by Jancálek et al (2010) in experimental models of peripheral neuropathy. Furthermore, TRPV1 receptor sensitivity to endogenous and exogenous ligands may be modulated by TNFα pretreatment, resulting in increased nociceptive signal transmission (Khan et al, 2008;Spicarova and Palecek, 2009).…”
Section: Discussionsupporting
confidence: 62%